2012
DOI: 10.1155/2012/673096
|View full text |Cite
|
Sign up to set email alerts
|

miRNA589 Regulates Epithelial-Mesenchymal Transition in Human Peritoneal Mesothelial Cells

Abstract: Background. microRNA (miRNA, miR) are thought to interact with multiple mRNAs which are involved in the EMT process. But the role of miRNAs in peritoneal fibrosis has remained unknown. Objective. To determine if miRNA589 regulates the EMT induced by TGFβ1 in human peritoneal mesothelial cell line (HMrSV5 cells). Methods. 1. Level of miR589 was detected in both human peritoneal mesothelial cells (HPMCs) isolated from continuous ambulatory peritoneal dialysis (CAPD) patients' effluent and HMrSV5 cells treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Recent evidence suggested that miRNAs contribute greatly to EMT, especially to the EMT of PMCs. This provided critical new information that advanced the knowledge of peritoneal fibrosis [11,12]. MiRNAs are distributed in a tissue-and timespecific manner, but their roles in the MGO-induced EMT of PMCs in vivo have not been explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggested that miRNAs contribute greatly to EMT, especially to the EMT of PMCs. This provided critical new information that advanced the knowledge of peritoneal fibrosis [11,12]. MiRNAs are distributed in a tissue-and timespecific manner, but their roles in the MGO-induced EMT of PMCs in vivo have not been explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 TGF- β 1 is known to have a pathogenetic role in the MMT in states of PD dysfunction. 1,1012 However, the mechanism(s) by which TGF- β 1 induces MMT in PD dysfunction remains to be clearly defined.…”
mentioning
confidence: 99%
“…1315 Recent studies indicate that miRNAs may contribute to the process of EMT in PD dysfunction 10,16,17 as well as in development of fibrosis. 1820 For example, miR-30 and miR-589 have been reported to be associated with the MMT process and peritoneal fibrosis in certain models of PD 10,16 , suggesting that miRNA may h ave a critical role in the pathogenesis of TGF- β -induced fibrosis in PD.…”
mentioning
confidence: 99%
“…Ultraviolet spectrophotometry was used to determined the content of peptides [6]. the maximum absorption peak (OD1) of polypeptide solution was determined by using ultraviolet spectrophotometer at the full wavelength to determine the maximum absorption peak (OD1) of polypeptide solution.…”
Section: Determination Of Decolorizing Ratementioning
confidence: 99%